(untitled) (Economic and Political Thought, 2015)
The concepts of differentiated integration in the EU emerged as a result of increasing diversification defined in terms of an economic development level, cultural heritage and nations’ political and social preferences. The principle of flexibility, which was applied to establish the countries of the ‘hard core’, allows the EU Member States to implement their enhanced cooperation. Therefore, the principle is considered to be the main ‘instrument’ for ‘differentiated integration’. The idea of a ‘two-speed’ Europe creates another category of the EU Member States, which should be supported economically in order to prevent the ‘hard core’ countries from strengthening.